El hamlet de fin del milenio : la crisis del mundo de la semejanza por el mundo de la representación, mediante el simulacro (2003)
ABSTRACT: The article aims at catchning a glimpse of how Hamlet, or Shakespeare, have addressed their times and now address ours; to what extent the different meanings of the text acquire a new meaning in our context. Image-thought, as inscribed in the text, is traced, showing how the world of similitude gives way to that of representation proper to the Renaissance, and how the latter leads to a world of order and historicity, as the great mechanism to catch a glimpse of transcendence, the beyond, after the play, after the shot